Pengaruh Jus Jambu Biji Merah terhadap Kadar Hemoglobin pada Remaja Putri di Universitas ‘Aisyiyah Yogyakarta - Natasya Riskya Aprilianti; Andri Nur Sholihah (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2025)
In Indonesia, anemia affects 21.7% of the population; 18.4% men and 23.9% women suffer from the condition. In accordance with the criteria, it reaches 26.4% at ages 5–14 and 18.4% at ages 15–25. Factors that contribute to anemia in adolescent girls include excessive iron loss, excessive blood loss, irregular menstrual cycles and iron insufficiency. There are two techniques to cure anemia, namely : pharmacological and non-pharmacological. This study sought to ascertain how red guava juice affected the hemoglobin levels of teenage girls at 'Aisyiyah Univeristy Yogyakarta. A quasi-experimental design with a single group pretest-posttest is used in this study. Total sample was 30 respondents. Intervention was juice of guava 150 mg on 100 ml water. Red guava juice improves hemoglobin levels in teenagers, as demonstrated by the paired t-test findings, which reveal a P value of 0.000 where the P value0.05. Ha was accepted and Ho was refused. Conclusion was red guava improve hemoglobin levels in teenagers.